Peran Pendidikan Islam dalam Membentuk Etos Kerja Profesional di Era Digital - Muhamad Darmawan Abdul; Hilman Mauludin; Akhmad Roziqin (PT. Pusmedia Group Indonesia, 2025)
Islamic education has a strategic role in shaping individuals who not only have academic competence, but also strong moral and spiritual values. This study aims to analyze how Islamic education contributes to building a professional work ethic based on Islamic values, such as discipline, honesty, responsibility, and hard work. The research method used is research with a literature review approach.The results of the study indicate that the concept of work ethic in Islam is based on the teachings of the Qur'an and Hadith, which emphasize the importance of working as part of worship and trust. In addition, Islamic education through a character-based curriculum, teacher role models, and technology integration in learning is able to shape professional and moral individuals. Thus, Islamic education plays an important role in preparing human resources who are not only superior in technical skills, but also have high morality in the digital era. Keywords: Islamic Education; Work Ethic; Professionalism; Digital Era